Taxonomic Identification of Boswellia dalzielii Hutch Based on Chemical composition - Abdulrahman Mahmoud Dogara; Aisha Abdullahi Mahmud; Bawale Sani Halliru; Isah Labaran; Hussaini Danlami (International Journal of Applied Biology, 2023)
Abstract The family Burseraceae comprises a total of 18 genera and 540 species. Boswellia dalzielii is a botanical species commonly employed in tropical and subtropical regions for its therapeutic properties, serving as a remedy for a diverse range of health conditions. The taxonomic identification and chemical composition of B. dalzielii in northern Nigeria have not been extensively documented in scientific literature, despite the recognized medicinal efficacy of this plant species. The soxhlet extraction method was employed to extract ethanol, methanol, and aqueous crude from the leaves. Subsequently, the extracted samples were subjected to analysis using gas chromatography combined with mass spectrometry. Fourier Transform Infrared spectroscopy (FTIR) was employed for the purpose of functional group identification in the crude extract. There was clear and noticeable distinction between the species under consideration on the X axis of principal component (PC) 1. The methanol and aqueous chemicals that were extracted from B. dalzielii showed a higher degree of similarity and were found to cluster together on the left side of the PC1 axis. PC2 did not indicate a clear distinction of the extract. The ethanol extract included 15 different chemicals, the methanol extract contained 12 different chemicals, and the aqueous extract contained 11 different chemicals.